Identification of taste receptors and proteomic characterization of the antenna and legs of Tribolium brevicornis, a stored food product pest. Issue 1 (6th November 2013) - Alabi, T.; Marion‐Poll, F.; Danho, M.; Mazzucchelli, G. D.; De Pauw, E.; Haubruge, E.; Francis, F.
Abstract Chemoreception plays an important role in mediating a diverse range of behaviours, including predation and food selection. In the present study, we combined anatomical observations, electrophysiology and proteomics to investigate sensilla that mediate chemoreception on the antenna and the legs of Tribolium. Scanning electron microscopy was used to differentiate the coxal and trochanteral segments of the pro‐, meso‐ and metathoracic legs by the presence of sensilla trichoidea and chaetica, while the antennae were covered with five types of sensilla (chaetica, basiconica, trichoidea, squamiformia and coeloconica). Antenna morphology and ultrastructure were similar in both sexes. Electrophysiological recordings allowed us to characterize a row of small sensilla basiconica on the terminal segment of the antenna as taste receptors, responding to sucrose and NaCl. Proteomics investigations of antennae and legs yielded several proteins with specific interest for those involved in chemoreception. Odorant‐binding proteins were antenna‐specific, while chemosensory proteins were detected in both tissues.